Understanding organizational resilience in elite sport: An exploration of psychosocial processes. (September 2022) - Fasey, Kirsten J.; Sarkar, Mustafa; Wagstaff, Christopher R.D.; Johnston, Julie
Abstract: Objectives: Although organizational resilience research has identified the characteristics of elite sport organizations that successfully deal with significant change, further research is needed to understand how they function. The objective of this study was to explore the psychosocial processes underpinning organizational resilience in elite sport. Design and method: Using interviews supplemented by timelines compiled from documentary analysis of public online sources, data was gathered during 43 interviews with 22 participants from 10 elite sport organizations across an 8-month period. Participant roles included chief executive officers ( n = 5), directors ( n = 7), board members ( n = 2), middle managers ( n = 4), support staff ( n = 2), head coach ( n = 1), and senior athlete ( n = 1). Reflexive thematic analysis of the data was conducted from a critical realist standpoint. Results: The data analysis yielded two core processes of sensing (internal and external mechanisms, diversity of perspectives, evaluating and monitoring) and adapting (mirroring current resource availability, open and frequent communication, acute versus chronic change), and two supporting processes of strengthening resources (quality and quantity of human and financial resources, relationships as source of additional resources) and shielding from risk (internal risk mitigation, external influencing). These data were interpreted to indicate that these processes are not sequential, or temporally distinct, but instead cumulatively contribute towards an organization's resilience capability. Conclusions: As the first empirical investigation exploring the psychosocial processes underpinning organizational resilience in elite sport, the results provide a unique framework and practical implications to help those working in and with elite sport organizations successfully navigate uncertainty and change. Highlights: Organizational resilience processes were explored with 10 elite sport organizations. Qualitative data were analysed using reflexive thematic analysis. Findings revealed two core and two supporting processes of organizational resilience. Data analysis yielded two core iterative processes of sensing and adapting. The two supporting processes were strengthening resources and shielding from risk.